2021
DOI: 10.3390/brainsci11050539
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Physiological Parameters and Colour Modifications in Text Background and Overlay during Reading in Children with and without Dyslexia

Abstract: Reading is one of the essential processes during the maturation of an individual. It is estimated that 5–10% of school-age children are affected by dyslexia, the reading disorder characterised by difficulties in the accuracy or fluency of word recognition. There are many studies which have reported that coloured overlays and background could improve the reading process, especially in children with reading disorders. As dyslexia has neurobiological origins, the aim of the present research was to understand the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…The authors suggested the importance of carrying out studies on dyslexia combining both neurophysiological and eye gaze data. Jakovljevic et al [ 80 ] studied the effect of colored overlays and backgrounds in 18 dyslexic Serbian children and 18 controls combining different oculomotor markers and neural oscillatory responses. They showed that the dyslexic children presented not only abnormal oculomotor patterns but also higher values of frequency bands (e.g., beta between 15 and 40 Hz) with purple overlay.…”
Section: Eye Movement Recordings In the Dyslexic Populationmentioning
confidence: 99%
“…The authors suggested the importance of carrying out studies on dyslexia combining both neurophysiological and eye gaze data. Jakovljevic et al [ 80 ] studied the effect of colored overlays and backgrounds in 18 dyslexic Serbian children and 18 controls combining different oculomotor markers and neural oscillatory responses. They showed that the dyslexic children presented not only abnormal oculomotor patterns but also higher values of frequency bands (e.g., beta between 15 and 40 Hz) with purple overlay.…”
Section: Eye Movement Recordings In the Dyslexic Populationmentioning
confidence: 99%
“…Brain-imaging methodology most prominently focuses on functional magnetic resonance imaging during reading [15,16] and diffusion tensor imaging [16,17], which both show, respectively, the functional or morphological differences between the dyslexic and the control group. Brain activity can be monitored using electroencephalography (EEG) as well, either on its own [18][19][20] or in combination with other biometric signals, such as heart rate, electrodermal activity (EDA), and eye tracking [21][22][23][24].…”
Section: Related Workmentioning
confidence: 99%
“…The data analysis in this paper was conducted on the dataset described in our previous research [22,41]. The data were gathered from 30 subjects, 15 diagnosed with dyslexia and 15 control subjects (age: 7-13, gender: 19 female, 11 male), during a study approved by the ethical committee of the Psychology Department of the University of Niš (a branch of the Serbian Psychology Association), experimental procedure No.…”
Section: Dataset and Experiments Descriptionmentioning
confidence: 99%
“…Most studies compared the EEG and the performance of DD and control children in linguistic, reading, or cognitive (Go-noGo, attention, reasoning, etc.) tasks Flynn & Deering, 1989a, 1989bFlynn et al, 1992;Galin et al, 1988Galin et al, , 1992Jakovljević et al, 2021;Klimesch et al, 2001;Leisman, 2002;Mahmoodin et al, 2016;Ortiz et al, 1992;Penolazzi et al, 2008;Remschmidt & Warnke, 1992;Rippon & Brunswick, 2000;Seri & Cerquiglini, 1993;Spironelli et al, 2006Spironelli et al, , 2008Taskov & Dushanova, 2020Žarić et al, 2017). A smaller number of other studies evaluate several other tasks: writing, speech, spelling, music, during the vision of an audio story, listening, and tapping (Colling et al, 2017;Di Liberto et al, 2018; Fig.…”
Section: Eeg During a Taskmentioning
confidence: 99%